Product Roadmap Planning in Dynamic Markets - Siddhey Mahadik; Umababu Chinta; Vijay Bhasker Reddy Bhimanapati; Prof.(Dr.) Punit Goel; Prof.(Dr.) Arpit Jain (Innovative Research Thoughts, 2023)
In the quickly changing business environment of today, product roadmap planning has become an essential component of organisational strategy. This is especially true in dynamic markets that are characterised by fast technology breakthroughs, altering customer tastes, and strong competitive challenges. This article looks into the complexities of product roadmap planning within such unpredictable marketplaces, analysing the most important tactics, best practices, and obstacles that are encountered by organisations that are attempting to retain a competitive advantage. Product roadmaps are strategic blueprints that explain the vision, direction, and advancement of a product across time. They are used to plan the product's development. For these roadmaps to be effective in dynamic marketplaces, they need to be flexible and forward-looking, able to accommodate developments that are both anticipated and unexpected. The purpose of this article is to investigate the fundamental elements that constitute efficient product roadmap planning, with a particular focus on the importance of adaptability and agility in the face of changes in the market. Finding a way to strike a balance between short-term and long-term aims is one of the most significant issues that dynamic marketplaces provide. Companies have to find a way to negotiate the conflict that exists between the urgent requirements of their customers and their wider strategic goals. The implementation of iterative development, periodic appraisal of market trends, and the inclusion of consumer input into the roadmap are some of the strategies that are discussed in this article as potential methods for striking this balance.